If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 12(x + -9) = 82 Reorder the terms: 8x + 12(-9 + x) = 82 8x + (-9 * 12 + x * 12) = 82 8x + (-108 + 12x) = 82 Reorder the terms: -108 + 8x + 12x = 82 Combine like terms: 8x + 12x = 20x -108 + 20x = 82 Solving -108 + 20x = 82 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '108' to each side of the equation. -108 + 108 + 20x = 82 + 108 Combine like terms: -108 + 108 = 0 0 + 20x = 82 + 108 20x = 82 + 108 Combine like terms: 82 + 108 = 190 20x = 190 Divide each side by '20'. x = 9.5 Simplifying x = 9.5
| 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 | | 5/6*2/3*2/7 | | x=(2.4e)/(0.68^1/5) | | 3/5*4/7*1/3 | | -9x^2+16x-14=0 | | 5(2x+3)=7(x+1) |